Factors Affecting Financial Distress in Trading Companies Listed on The Indonesia Stock Exchange - Aini, Syelvi Nurul; Wahyudi, Ickhsanto (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the effect of the debt-to-asset ratio (DAR), business strategy, board of directors, and earnings management on financial distress in trading companies listed on the Indonesia Stock Exchange during the 2022–2024 period, with firm size serving as a moderating variable. This study employed a quantitative approach using secondary data in the form of companies' financial statements obtained from the official website of the Indonesia Stock Exchange. The sample consisted of 36 companies selected from a population of 62 through a purposive sampling technique, resulting in 108 observations. Data were analyzed using descriptive statistics, panel data regression, and Moderated Regression Analysis (MRA), with model selection conducted through the Chow test and Hausman test. The results indicate that DAR has a negative and significant effect on financial distress, while business strategy has a positive and significant effect on financial distress. Meanwhile, the board of directors and earnings management do not have a significant effect on financial distress. In addition, firm size is not able to moderate the effect of DAR on financial distress. This study is expected to provide useful insights for management and investors in understanding the factors that influence the risk of financial distress.